Cardiac operations and interventions during the COVID-19 pandemic: a nationwide perspective. (24th May 2021) - Leyva, F; Zegard, A; Okafor, O; Stegemann, B; Ludman, P; Qiu, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Aims: The COVID-19 pandemic has led to a decline in hospitalizations for non-COVID-19 related conditions. We explored the impact of the COVID-19 pandemic on cardiac operations and interventions undertaken in England. Methods: An administrative database covering hospital activity for England, the Health Episodes Statistics, was used to assess a total of 286, 697 hospitalizations for cardiac operations and interventions, as well as 227, 257 hospitalizations for myocardial infarction (MI) and 453, 799 for heart failure (HF) from 7th January 2019 to 26th July 2020. Results: Over the 3 months of 'lockdown', total numbers and mean reductions in weekly rates (n [-%]), compared with the same time period in 2019, were: coronary artery bypass grafting (-2507 [-64%]); percutaneous coronary intervention (-5245 [-28%]; surgical (-1324 [-41%]) and transcatheter (-284 [-21%]) aortic valve replacement; mitral valve replacement; implantation of pacemakers (-6450 [-44%]), cardiac resynchronization therapy with (-356 [-42%]) or without (-491 [-46%] defibrillation devices, and implantable cardioverter defibrillators (-501 [-45%]); atrial fibrillation ablation (-1902 [-83%]), and other ablations (-1712 [-64%]) (all p < 0.001). Over this period, there were 21, 038 fewer procedures than in the reference period in 2019 (p < 0.001). These changes paralleled reductions in hospitalizations for MI (-10, 794 [-27%]) and HF (-63, 058 [-28%]) (both p < 0.001). Conclusions: The COVID-19 pandemic has led to substantial reductions in the number of cardiac operations and interventions undertaken. An alternative strategy for healthcare delivery to patients with cardiac conditions during the COVID-19 pandemic is urgently needed.